2003
DOI: 10.1523/jneurosci.23-06-02019.2003
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Excitatory and Inhibitory GABA Synapses in the Cerebellar Interneuron Network

Abstract: Functional GABA synapses are usually assumed to be inhibitory. However, we show here that inhibitory and excitatory GABA connections coexist in the cerebellar interneuron network. The reversal potential of GABAergic currents (E GABA ) measured in interneurons is relatively depolarized and contrasts with the hyperpolarized value found in Purkinje cells (Ϫ58 and Ϫ85 mV respectively). This finding is not correlated to a specific developmental stage and is maintained in the adult animal. E GABA in interneurons is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(181 citation statements)
references
References 47 publications
14
166
0
1
Order By: Relevance
“…Another possibility is the excitatory nature of some GABA A receptors. It has been shown that GABA A receptor-mediated synaptic responses are not always inhibitory, and can be excitatory even in adult animals under normal conditions [31][32][33]. Blocking such excitatory GABA A receptors (if they were involved in the oscillation generation in our recordings) could also be responsible for reduction of the CA1 oscillation.…”
Section: Discussionmentioning
confidence: 70%
“…Another possibility is the excitatory nature of some GABA A receptors. It has been shown that GABA A receptor-mediated synaptic responses are not always inhibitory, and can be excitatory even in adult animals under normal conditions [31][32][33]. Blocking such excitatory GABA A receptors (if they were involved in the oscillation generation in our recordings) could also be responsible for reduction of the CA1 oscillation.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, neurophysiologists have gone to elaborate measures in order to determine whether GABA-mediated synaptic potentials are hyperpolarizing or depolarizing at rest (e.g. Verheugen et al, 1999;Chavas and Marty, 2003). Although tight-seal cell-attached recording cannot provide the numerical value of the reversal potential of a synaptic event, it does accurately depict the direction of the synaptic potential (i.e.…”
Section: Part Iv: Discussion Of the Advantages Of Cell-attached Recormentioning
confidence: 99%
“…The only differences between the equations presented here and those of Mason et al (2005) are the inclusion of the cell membrane resistance (R cell ) and the liquid junction potential (E lj ) between the electrode solution and the bath solution. R cell is included here because Tyzio et al (2003) and Chavas and Marty (2003) have convincingly described how R cell affects the accuracy of the measured membrane potential in perforated patch and whole-cell recordings when there is a finite R seal . The same reasoning applies to cell-attached recordings.…”
Section: Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Most instances of depolarizing GABA actions during nonpathological states have been reported after intense or prolonged activation of GABA A receptors Nicoll, 1979, 1982;Staley et al, 1995;Kaila et al, 1997), and are thought to result from a breakdown of the chloride gradient, followed by efflux of bicarbonate anions through open GABA A channels (Staley et al, 1995). However, two recent studies have reported increased postsynaptic spiking after single-pulse stimulation of GABAergic neurons in adult cerebellum (Chavas and Marty, 2003) and cortex (Gulledge and Stuart, 2003).…”
Section: Introductionmentioning
confidence: 99%